PENERAPAN PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING UNTUK PENETAPAN HARGA JUAL Pada Pabrik Tahu “Feri Irawan” Desa Pakusari - Santoso, Moch; Yuliarti, Norita Citra; Afroh, Ibna Kamelia Fiel (Fakultas Ekonomi dan Bisnis, 2023)
Many factories or companies do not have proper financial records, especially in calculating the cost of production. Though the calculation is needed in order to facilitate the company in determining the selling price. The method used to calculate the cost of tofu production in this study is the full costing method because in this method it is required to include all costs incurred in the production process, including fixed overhead costs and variable overhead costs. This study uses a descriptive qualitative approach where the aim is to explain systematically the research focus which includes calculating the cost of production using the full costing method and determining the selling price based on the cost plus pricing method. The object of this research is the tofu factory. Data was collected by means of observation, interviews, and documentation. From the results of the study indicate that the calculation of the cost of production based on the full costing method produces higher costs than the calculation according to the company. This is because the company has not included all the cost components incurred for the production process, such as variable overhead costs and non-production costs. So that also experienced an increase in setting the selling price.